(untitled) (Indian Journal of Public Health Research & Development, 2020)
Background- One of the most important determinants of the quality of life of older people is their functional health status that refers to their capacity to perform normal daily activities. With the advent of globalization and changing family structures, there are elderly who are left alone to fend for themselves without any formal support. Aim & Objective: to find out the evolving patterns of adjustment in the absence of care giver of elderly who are living alone in Delhi/ NCR. Material and Method: The study is carried under descriptive research design. One Household Proforma was used for the purpose of obtaining their demographic information and a pretested scale is used to elicit the information on their IADL after taking consent from the elderly. Snowball sampling technique is incorporated for data collection. Data is collected from a structured questionnaire and Focus Group Discussions with 80 respondents above the age of 60 years, living alone from Delhi/NCR to find their adjustment patterns. Result: the results show that respondents are independent for their ADL and IADL and in case of dependency the respondents have two types of support- support on daily basis i.e, house-help and support available for in absentia of routine care takers i.e, their kin living in the vicinity and elderly groups formed in the community. Conclusion: The respondents have formed their own community networks that provide assistance to them in case of need or they reconcile to avoidance.